Determinants of foreign trade conflicts - KALYUZHNA Наталія (Ius Modernum, 2019)
Background. The dual nature of modern foreign trade relations is determined by the priority of protecting national interests in the multipolar world geopolitical system. As a result of the dominance of foreign policy goals over foreign economic activity, the intensification of interstate trade conflicts with possible intensification of them to the stage of trade and economic wars has become a thing of the past. The analysis of recent researches and publications. Mostly researchers identify any interstate trade conflict with trade war, which in general is defined as a process of opposing economic or political interests in order to achieve the desired results using various protectionist regulative tools. However, the differences in the process of this confrontation are evident in view of the different intensity of interstate tension. The level of the tension has different consequences for the foreign trade and foreign policy relations of the countries, and provides for regulatory measures of varying rigidity. The aim of the article is to systematize the terminology in the field of study of interstate trade conflicts and to identify the stages of contradictory foreign trade relations between the states in view of its intensity. Materials and methods. Methods of analysis and synthesis are used to systematize the stages of contradictory foreign trade relations between states in view of the intensity of tension; methods of comparison and generalization – to substantiate the key features of the trade war as a trade-off conflict of maximum intensity. The research based on scientific publications and materials of the World Trade Organization. Results. The article systematizes the terminological apparatus in the field of study of interstate trade conflicts, which includes the concepts: controversial situation in trade, trade disputes, trade conflict, and trade war. The stages of contradictory interstate foreign trade relations between states entities are described in accordance with characteristics such as the deterioration of trade conditions, the intensity of interstate tension, the type of relations, economic losses, and the impact on other states, implementation tools, political subtext, and settlement instruments. The expediency of considering the intensity of tension as the determinant of foreign trade conflicts is substantiated. The key features of the trade war as a foreign trade conflict of maximum intensity are systematized. The trade war is determined as a systemic dynamic trade-off conflict of maximum intensity of tension, which has a political background and needs the complex application of restrictive foreign trade policy instruments such as trade economic sanctions. Other contradictions in foreign trade (depending on the intensity of interstate tension and other criteria) may be attributing to the previous successive stages of the contradictory foreign trade relations, namely: the contradictory situation in trade, trade dispute, and trade conflict. Conclusion. The efficiency of resolving foreign trade conflicts directly depends on the willingness of the parties to the conflict to resolve or further intensify it. The absence of action to resolve conflicts leads to its escalation to the stage of trade wars, which means significant economic losses both for the parties to the conflict and for the global economy as a whole.